2021
DOI: 10.1155/2021/1056659
|View full text |Cite
|
Sign up to set email alerts
|

Eales’ Disease: When the Rare Sounds Frequent

Abstract: Eales’ disease is a peripheral occlusive retinal phlebitis, with an unclear pathogenesis. The classic association with hypersensitivity to Mycobacterium tuberculosis protein infers that immunologic disturbance may be involved. Here, we described three cases of Eales’ disease. All patients are Caucasian men aged 27-58 years and presented with vitreous hemorrhage and/or peripheral venous vasculitis. Tuberculin skin sensitive test (Mantoux screening test) and interferon-gamma release assay (IGRA) were positive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…A fundus examination revealed similar findings in our patient along with a vitreal hemorrhage and thick epimacular membrane. Lopes et al reported similar findings in a series of three Eales disease cases [ 11 ].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…A fundus examination revealed similar findings in our patient along with a vitreal hemorrhage and thick epimacular membrane. Lopes et al reported similar findings in a series of three Eales disease cases [ 11 ].…”
Section: Discussionsupporting
confidence: 69%
“…The disease is most common in young male adults and it is usually bilateral. Asymmetrical involvement of the eyes has been reported; the disease can unilaterally manifest in the early stages, but usually both eyes are involved as the disease progresses [ 1 , 11 , 17 ]. Nicolcescu et al reported the case of a 48-year-old woman with unilateral Eales disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the above classes of microbes have been associated with intermediate uveitis (90,(128)(129)(130)(131)(132). Latent tuberculosis has been implicated in peripheral occlusive retinal vasculitis (previously known as Eales' disease) (133)(134)(135), while latent EBV infection is a strong candidate for the same pathology in MS (84,136). Pars planitis with or without snowbanking has been linked to parasitic infections such as toxocariasis (137) while vitritis has long been associated with low level infections with mycoplasma and other cell wall deficient bacteria (138,139).…”
Section: Intermediate Uveitismentioning
confidence: 99%